(3ehUd GdWdGH Edi bhGYO GdEYQGHs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s ((3YHO GddWja Hf EHQGgje GdYeGOjs)
(3ChdgG (B:s
(3GdMeO ddg Gdedge dMeOg hHYO ajbhdNGdO Hf YHO Gddg GdCRgQj gPG TQM dWja Ydi bhGYO GdEYQGH SejJg ehUd GdWdGH Edi bhGYO GdEYQGH HSe Gddg GdQMef GdQMje GdHGA eJYdbI HaYd eMPha JbOjQg CaJJMs
(3BNQgG (B:s
(3haj gPG GdbOQ GdPj PcQg GdeUfa GdeUfa caGjI def JCed aEf GdJCed CUd aj OQc GdCehQ adPdc MV Ydi GdJCed aj NJe GdcJGH ceG aYd aj GaJJGMg bGd fbJVj HeJCedgG LGOI GdUhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 297s
(3eYLe GdeDdajf(B: 8 / 26s
(3cTa GdXfhf(B: 1 / 124s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs